From Drought to Abundance: Stories of Transformational adaptation: How a solar-Powered borehole transformed an Indigenous Tonga community in Zambia - Monze, Hanzila; Amarnath, Giriraj; van Koppen, Barbara; Mweemba, Carol (CGIAR System Organization, 2024)
The document details the transformative impact of locally led adaptation approaches in Hanzila, a community in Zambia's Southern Province. Implemented through CGIAR's ClimBeR initiative in response to the devastating EL Nino-induced drought of 2024. The intervention addressed water scarcity, enabling access to clean water for over 900 households and their livestock, while supporting crop irrigation. This has improved food security, diversified incomes, and reduced gendered labor burdens. The story underscores the significance of polycentric governance and participatory decision-making in climate resilience efforts. By empowering locl communities, particularly women, the initiative exemplifies sustainable adaptation practices, demonstrating the pivotal role of water access in enhancing livelihoods and buffering against climate shocks.